Molecular and clinical characterization of de novo and familial cases with microduplication 3q29: guidelines for copy number variation case reporting - Goobie, S. (S. Karger AG, 2009)
Microdeletions of 3q29 have previously been reported, but the postulated reciprocal microduplication has only recently been observed. Here, cases from four families, two ascertained in Toronto (Canada) and one each from Edinburgh (UK) and Leiden (Netherlands), carrying microduplications of 3q29 are presented. These families have been characterized by cytogenetic and molecular techniques, and all individuals have been further characterized with genome-wide, high density single nucleotide polymorphism (SNP) arrays run at a single centre (The Centre for Applied Genomics, Toronto). In addition to polymorphic copy-number variants (CNV), all carry duplications of 3q29 ranging in size from 1.9 to 2.4 Mb, encompassing multiple genes and defining a minimum region of overlap of about 1.6 Mb bounded by clusters of segmental duplications that is remarkably similar in location to previously reported 3q29 microdeletions. Consistent with other reports, the phenotype is variable, although developmental delay and significant ophthalmological findings were recurrent, suggesting that dosage sensitivity of genes located within 3q29 is important for eye and CNS development. We also consider CNVs found elsewhere in the genome for their contribution to the phenotype. We conclude by providing preliminary guidelines for management and anticipatory care of families with this microduplication, thereby establishing a standard for CNV reporting.